Effect of Ge diffusion on AlxGa1-xN/GaN high electron mobility transistors on a thin silicon-on-insulator - Bera, L. K. (2014)
In this letter, the effect of Ge diffusion at the gate area of AlxGa1-xN/GaN high electron mobility transistors (HEMTs) on a thin silicon-on-insulator (SOI) substrate has been investigated. The pinch-off voltage shifted toward enhancement mode type operation behavior due to the Ge diffusion through the surface of the thin GaN cap layer. An anomalous hump observed in high frequency C-V plot is due to the electron confinement at the Ge-GaN/AlGaN interface. The threshold voltage reduces by 0.8 to 1.0 V after Ge diffusion. The drive current and the transconductance further reduced as compared to the control sample due to the parallel channel formation at the top Ge-GaN/AlxGa1-xN interfaces.